Factors Related to Acceptance of Going Concern Audit Opinion in Banking Companies - Putu Kepramareni; Sagung Oka Pradnyawati; Ni Kadek Ayuni Astari (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
The continuity of the banking business in Indonesia is of great concern considering the important role of banking for the economy, especially during difficult times such as during a pandemic. In banks that have gone public, a going concern audit opinion is one of the audit opinions to avoid because it relates to doubts about the going concern of a business entity, so it is important for business entities, especially banks, to pay attention to every factor that can influence it both in terms of firm size, capital, the growth of bank assets is related to the profit and soundness of the bank from the LDR (loan to deposit ratio) side where the author tests these related factors. This study aims to examine the factors related to acceptance of going concern audit opinion in banking companies. A total of 43 banking companies were used as samples and tested using logistic regression. Based on the test results, it was revealed that there is a negative effect on the receipt of a going concern audit opinion on firm growth. Factors viewed from the side of firm size, LDR, capital and firm profits did not show any effect on acceptance of going concern audit opinions in the banking companies studied.